AI vs. Clinical Diagnosis: A Professional Analysis of Reliability in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into healthcare represents a significant paradigm shift. At its core is the diagnostic process, where AI promis...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care